Spatial and temporal changes in male gypsy moth wing morphology reflect host tree phenology and habitat quality. (30th July 2020) - Jahant‐Miller, Chelsea; Tobin, Patrick C.; Parry, Dylan
Abstract: The size of adult gypsy moths, ( Lymantria dispar L.), a capitalbreeder, is correlated with environmental conditions experienced as larvae. Proxies for adult size such as wing length may provide information about habitat quality and population density. We used male gypsy moths collected from pheromone traps at intervals through the flight season to assess phenological change in wing length. Consistent with a previous study conducted at our reference site, we found that wing length declines seasonally, likely resulting from phenological reduction in host foliage quality. This pattern was evident at our reference site over 8 years, and at our experimental sites with low‐density populations in 3 years. We assessed forest quality using two unique metrics, basal area of red oak (Quercus rubra), a high quality host tree, and a composite value generated from a published ranking of tree species quality for gypsy moth. We did not find a relationship between these metrics and wing length, although we found that the mean size of males was larger in stands with oak. Mean wing length in outbreak populations was significantly smaller reflecting density related processes such as intraspecific competition, although there was no significant seasonal effect on wing length. Abstract : Consistent with a previous study conducted at our reference site, we found that wing length declines seasonally, likely resulting from phenological reduction in host foliage quality. Mean size of males trapped in oak‐present forests was significantly greater than in oak‐absent forests; however, there was no significant relationship between male wing size and continuous metrics of gypsy moth habitat quality. Mean wing length in outbreak populations was significantly smaller reflecting density related processes such as intraspecific competition, although there was no significant seasonal effect on wing length.